Drill-exit temperature characteristics in drilling of UD and MD CFRP composites based on infrared thermography. (December 2018) - Fu, Rao; Jia, Zhenyuan; Wang, Fuji; Jin, Yan; Sun, Dan; Yang, Lujia; Cheng, De
Abstract: This paper presents a comprehensive study on the complex drill-exit temperature characteristics in the drilling of unidirectional (UD) and multidirectional (MD) CFRPs using a state-of-art microscopy infrared imaging system. For the first time, temperature variation and distribution at drill exit have been revealed in full detail, associated with the CFRP material properties and drilling conditions. Results suggest that the actual drill/CFRP interactions have critical but similar effects on the drill-exit temperatures for UD and MD CFRPs. Specifically, three distinct cutting regions with varying temperature characteristics are evident when the main cutting edge is acting on the drill exit material. In all cases, the temperature distribution features elliptical shape, of which the eccentricity depends on the lay-up sequence and the drilling depth. In addition, the real-time temperature profiles and 2D/3D maximum temperature distribution maps are created with high visualization. With the aid of those findings, the relationships between drilling temperature maxima, their locations and drilling depths have been discovered and temperature effects on drill-exit damages have been elucidated for the first time. MD CFRP is proven more difficult to achieve high drilling qualities at certain fiber cutting angles than UD CFRP due to the associated temperature effects. Such important knowledge enables the identification of the heat affected zones and subsequently informs strategies for reducing the negative temperature effects. Highlights: Drill/UD and MD CFRPs interactions have critical but similar effects on the temp. Max. Temp. is not on the highest cutting-speed area but within normal diameter. Temp. outside normal diameter peak during minor cutting edge acting on drill exit. Temp. distributions feature ellipse, varying with lay-up sequence/drilling depth. MD CFRP suffers more severe drilling damages at certain angles for temp. effects.